To evaluate the impact of aspirin in prevention of coronary artery disease in superspeciality hospital Jalandhar Punjab, India (International Journal of Current Research in Physiology and Pharmacology, 2023)
Introduction: Coronary artery disease (CAD), a prevalent cardiovascular ailment, arises from the gradual accumulation of fatty deposits, cholesterol, and other substances within the coronary arteries – the blood vessels responsible for supplying oxygen and nutrients to the heart muscle. Aspirin plays a pivotal role in the management of Coronary Artery Disease (CAD) due to its antiplatelet properties. CAD often involves the formation of blood clots within narrowed coronary arteries, potentially leading to heart attacks. Aspirin, a blood-thinning medication, helps prevent clot formation by inhibiting the aggregation of platelets, which are blood cells involved in clotting. Objective: The objective of this study was to the impact of aspirin in prevention of coronary artery disease in superspeciality hospital Jalandhar Punjab, India. Methodology: The study was conducted in cardiac care unit at Nasa and Hub Superspeciality hospital Jalandhar Punjab and exclusively on patients who presented with any kind of cardiac disorder symptoms. This study was approved by the Ethics committee of Nasa And Hub Superspeciality Hospital. All the subjects have signed the informed consent form. In this study, 200 patients were recruited in NASA AND HUB SUPERSPECIALITY HOSPITAL Jalandhar Punjab from 8th june 2022 to 8th September  2022. Results and Discussion: . In this study population, there were significant differences between male and female concerning cardiovascular risk factors, so cigarette smoking is very prevalent in young group and limited for males. We observed that hypertension and diabetes are present at high level in women than men, and the percentage of hypertension and diabetes increase in both gender with age. In the present study, we examined a representative sample of visits to physicians in the Nasa And Hub Superspeciality Hospital by patients with coronary artery disease, with a focus on visits to cardiologists and primary care physicians by patients in whom aspirin was not contraindicated. Conclusion: Aspirin continues to be the mainstay of antiplatelet therapy in individuals with coronary artery disease (CAD) in this observational study. Patients at a high risk of developing CVD in the future may be advised to take aspirin, but the potential for adverse effects must be recognised in addition to the advantages. As a result of our study, it is imperative to reinforce the need for proper coronary artery disease (CAD) management in order to prevent further coronary artery complications.Keywords: Coronary artery disease, aspirin, smoking, hypertension
Keywords: Coronary artery disease, aspirin, smoking, hypertension